The potential effects of anticonvulsant drugs on neuropeptides and neurotrophins in pentylenetetrazol kindled seizures in the rat. (1st February 2020) - Tekgul, Hasan; Simsek, Erdem; Erdoğan, Mumin Alper; Yiğittürk, Gürkan; Erbaş, Oytun; Taşkıran, Dilek
Abstract: Purpose: Neuropeptides and neurotrophic factors are thought to be involved in epileptogenesis. This study aims to investigate the potential effects of anticonvulsant drugs on neuropeptides (galanin and neuropeptide Y) and neurotrophic factors (BDNF and NGF) in pentylenetetrazol (PTZ)-kindled seizures in the rat. Methods: Forty-eight adult male Sprague–Dawley rats were included in the study. The animals were divided into 8 groups of six rats. Group 1 was defined as naïve control, and received no medication. Group 2 (PTZ + saline) was treated with sub-convulsive doses of PTZ (35 mg/kg) and saline i.p. for 14 days. For anticonvulsant treatments, Groups 3–8 were treated with 200 mg/kg levetiracetam (PTZ + LEV), 1 mg/kg midazolam (PTZ + MDZ), 80 mg/kg phenytoin (PTZ + PHT), 80 mg/kg topiramate (PTZ + TPR), 40 mg/kg lamotrigine (PTZ + LMT) and 50 mg/kg sodium valproate (PTZ + SV), respectively. All anticonvulsant drugs were injected 30 min prior to PTZ injection throughout 14 days. Following treatment period, behavioral, biochemical and immunohistochemical studies were performed. Results: PTZ + saline group revealed significantly decreased galanin, NPY, BDNF and NGF levels compared to control. PTZ + MDZ group had significantly increased galanin, BDNF and NGF levels compared to saline group. Also, PTZ + LEV group showed increased BDNF levels. PTZ + saline group revealed significantly lower neuron count and higher GFAP (+) cells in hippocampal CA1–CA3 regions. All anticonvulsants significantly reduced hippocampal astrogliosis whereas only midazolam, levetiracetam, sodium valproate and lamotrigine prevented neuronal loss. Conclusion: Our results suggested that anticonvulsant drugs may reduce the severity of seizures, and exert neuroprotective effects by altering the expression of neuropeptides and neurotrophins in the epileptogenic hippocampus.